PENGARUH BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA UNTUK MENCEGAH PERILAKU MENYONTEK SISWA KELAS VII SMP PGRI 1 SEMARANG - Aulia Alfiani; Heri Saptadi Ismanto; Agus Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education is one of the important factors in a person's life. The behavior of today's students is quite a public concern, besides being a serious problem, it is also our duty to make students more advanced. The purpose of this study was to determine the effect of group guidance with sociodrama techniques to prevent cheating behavior of class VII students of SMP PGRI 1 Semarang. The research used in this study was quantitative with the true experiment method. This study used a pretest-posttest control group design. Based on the results of the posttest of the experimental class and the control class. In the experimental class, the highest score was 97 and the lowest score was 80 while in the control class the highest score was 80 and the lowest score was 73. Based on the results of the calculation of the two-average difference test, the data presented in the table above is known in the Levene's test for equality of means column has a significant value of 0.001 (p> 0.05). Based on the results of the analysis, it can be concluded that there is an effect of group guidance with sociodrama techniques to prevent cheating behavior of class VII students of SMP PGRI 1 Semarang. From the results of the analysis obtained in the experimental class before the group guidance service with the sociodrama technique was carried out, the average pretest value of cheating behavior was 71.8 and after the group guidance service with the sociodrama technique was carried out, the average posttest value of cheating behavior increased, namely 88.6. Based on the results of the research that has been carried out, the researcher makes several suggestions, namely: Group guidance services with sociodrama techniques are very useful, so it is hoped that the school can implement the implementation of services with sociodrama techniques. Guidance and Counseling Teachers can develop new innovations using this sociodrama technique. Students who have participated in group guidance services with sociodrama techniques are expected to be able to maintain the commitments that have been made and can actualize themselves better.